Strategic Growth of Honey Pineapple Micro-Enterprises through IFE-EFE-QSPM Analysis - Tutik Tutik; Paiman Eko Prasetyo; Karsinah Karsinah; Mohammad Aulia Rachman; Aria Robi Falhala (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to formulate appropriate welfare improvement strategies through the analysis of internal and external factors and the identification of priority strategies using the QSPM. A quantitative descriptive approach was employed, with data collected through Likert-scale questionnaires, interviews, and direct observations. The IFE matrix produced a score of 2.86, indicating that internal strengths are relatively dominant, particularly in product quality and farmer networks. Meanwhile, the EFE matrix yielded a score of 3.12, suggesting that external opportunities remain substantial, especially in terms of increasing market demand and government support programs. The business position in the IE Matrix falls within Quadrant II, implying significant growth potential that requires targeted development strategies to capitalize on existing opportunities. The QSPM analysis identifies digital marketing training and branding enhancement as the top strategic priorities, followed by expanded access to financing, product quality certification, and strengthening farmer institutions. Overall, the findings confirm that improving the welfare of honey pineapple micro-entrepreneurs should be pursued through growth-oriented strategies that emphasize internal capability development, effective utilization of digitalization, and integrated, sustainable institutional support.